Partial Substitution of Teos with Pyridyl-Silanes: A Route to Functionalizing Inner Wall of Imogolite Nanotubes - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K; Silva-Molina, C; Silva-Molina, C; Flores-Salinas, C; Flores-Salinas, C (Elsevier Ltd, 2025)
A new imogolite isostructure (Imo-Py) was obtained and characterized structurally and superficially, where 5 % of the TEOS was replaced by 2-(4-pyridylethyl)triethoxysilane. Incorporating the new organosilane did not cause significant inhibitions to nanotubular formation. However, an increase in the diameter and reactivity of the internal cavity of Imo-Py compared to imogolite was evidenced, attributable to the differences in charge and acidity properties of the incorporated functional groups. This study expands the family of imogolite-based nanostructures and could contribute to new technological applications. © 2024